Â¬Design Of Acoustic Soundwave System For Fire Prevention - S.Mohanraj, P.Davidkumar, KR.Dhanavandan , SS.Tharun (International Journal of Modern Agriculture, 2021)
Apart from loss of living things and huge natural and private properties including large forest and houses and create a big threaten to environment. Here we use flame sensor to detect the fire that exists in the forest. If the flame sensor detects the fire, then it will give input to the micro controller. After the prediction of fire or smoke, should put-off the fire. For that here a new technology is used. That is fire is extinguished with the help of Sound waves. In general, fire is put off with the help of water or other chemical substance. As compared with other chemicals and classical extinguishers, this technique pays the way to put-off flames in cleanest way. Once we predict the fire by flame sensor. With the microcontroller ARDUINO UNO, a SD card is connected and which is storing the sound files. A speaker and amplifier circuit is connected with micro-controller. Once the micro- controller receives the data for fire detection from the flame sensor, the controller will read the sound files from SD card and generate the high frequency sound waves to put-off the fire.